PERMASALAHAN PENGGUNAAN YOUTUBE FAIR USE DALAM KASUS TOTALLY NOT MARK VS TOEI ANIMATION - Lie, Madeleine (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The case of Totally Not Mark vs. Toei Animation stole attention in the Youtube community back in 2021, when Toei Animation targeted Totally Not Mark with 150 separate copyright strikes on his channel, all manually filed by Japanese animation studio Toei Animation. According to the YouTuber, Toei Animation submitted YouTube direct takedown requests for all 150 videos, which may result in the content being removed from his channel instantly, as well as strikes that would end his channel entirely. YouTube apparently responded to such notices, asking Toei to clarify whether they had considered fair usage and requesting additional justification from Toei. This raised issues within the IP industry, where Youtube, a company based in the United States, recognizes fair use while Toei Animation, a company based in Japan, does not. According to YouTube, what Toei Animation did Instead of replying to YouTube's request for justification for their takedown notices, they used their own tools behind YouTube's back to manually claim and block every one of the 150 videos in the Totally Not Mark catalog of content. To summarize, Toei explicitly broke the rules in this case. However, if Toei Animation had used Japanese IP Law instead, YouTube would likely have honored their removal, removed the videos worldwide, and potentially struck out the Totally Not Mark channel.